Methylation patterns within 5′-UTR of DAT1 gene as a function of allelic 3′-UTR variants and their maternal or paternal origin: May these affect the psychopathological phenotypes in children? An explorative study. (20th November 2022) - Carpentieri, Valentina; Pascale, Esterina; Cerniglia, Luca; Pucci, Mariangela; D'Addario, Claudio; Laviola, Giovanni; Adriani, Walter; Cimino, Silvia
Highlights: Correlation between CpG methylation patterns is a novel approach to epigenetic analysis. We studied the DAT1 gene promoter, at two 5′-UTR motifs, as function of allelic 3′-UTR variants. Sample: DAT1 9/9, 10/10 and 9/10 born from a 10/10 and a 9/10 parent (if father: heF; if mother, heM). 9/9 homozygous children show internalizing symptoms and demethylated CpGs 1 and 6. First and second motifs of DAT1 5′-UTR serve a new biomarker for recognizing internalizing children. Abstract: Psychopathological symptoms such as depression/anxiety vs attention or aggression problems, in children, have been associated to altered expression of the DAT1/SLC6A3 gene. Inheriting specific 9- or 10-repeat VNTR alleles could modify the pattern of methylation in the CpGs islands at the 5′-UTR of the DAT1 gene. Through accurate recruitment at primary schools, we ended up with four subgroups of children: 9/9 and 10/10 homozygous; 9/10 heterozygous born from 9/10 mothers and 10/10 fathers (called heM); 9/10 heterozygous born from 10/10 mothers and 9/10 fathers (called heF). (Epi)genetical changes were found to be in relation to internalizing and externalizing symptoms: compared to other genotypes, our 9/9 children exhibited mainly internalizing symptoms, while 10/10 genotype was previously associated with ADHD severity. We found that 10/10 children bear 5′-UTR motifs showing a CpGs 1-2-3-5 unity with anticorrelated CpG 6, while 9/9 children showed rather a demethylated CpG 1 linked to demethylated CpG 6. We found two different patterns between heMs and heFs: a feature of heM children is in CpGs 1-3 methylated pattern with CpGs 2, 5 and 6 demethylated together, supporting a "split" unitary destiny. Within the heF children, the status for CpGs 3 + 6 remained opposite, yet pattern of (de)methylation was not well defined. The prevailing one between inherited parental alleles may somewhat influence the motif destiny of heterozigous children. Present work aimed to identify novel epigenetic biomarkers, to be exploited as fairly indicators of children's psychopathological vulnerability.